Enhancing governance in Indonesian legal entity state universities: Insights from global best practices - Siregar, Kardina Engelina; Putra, Ali Musri Semjan (Journal of Educational Management and Instruction (JEMIN), 2024)
In the context of higher education in Indonesia, Legal Entity State Universities (PTNBH) encounter substantial challenges in implementing effective governance. This study aims to analyze global best practices in university governance and apply these insights to enhance PTNBH governance in Indonesia. Through a comprehensive literature review and best practice analysis, this research identifies key factors contributing to successful governance in leading universities worldwide. Employing thematic and comparative analysis methods, the study evaluates the current governance of PTNBH and compares it with international best practices. The findings reveal that transparency, accountability, stakeholder participation, and managerial innovation are crucial elements of effective governance. Furthermore, the study proposes a framework for implementing best practices tailored to the unique context of PTNBH in Indonesia. The conclusions underscore the importance of adopting innovative and evidence-based governance strategies to enhance PTNBH's performance and competitiveness. Practical recommendations and policy implications are provided to assist policymakers and stakeholders in developing more efficient and responsive governance systems to address future challenges. This research contributes to the academic literature on higher education governance and offers practical insights for governance reform at PTNBH.